Poverty, Inequality and Health: A case study of Armenia - Tamara Tonoyan (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2005)
The paper describes the issue of the impact of poverty and income inequality on the health of the population using Armenia as a case study. In the framework of this paper author provides an overview of research relating to inequalities in health to the disadvantage of the poor, and to changes in impoverishment and income inequality associated with payments for health care. After demonstrating the logic of the investigation, the paper recapitulates the information about results of reforms that do not appear to meet all the objectives of health care policy. The paper indicates that the gains in freedom have been accompanied by the losses of many basic economic and social services that the population had come to enjoy and expect. At the same time the success of reforms applied in Armenia is often evaluated against improvements in the health status of the population. Funding shortages often means that even vulnerable groups have to pay. Thus, the principle of equity with respect to financing and access is undermined. It is emphasized that reducing poverty and income inequality should be grounded in a pro-poor growth approach, i.e. for equality to be achieved economic growth in the development process should be deliberately adapted to the needs of the poor. The paper concludes that there is undoubtedly a large gap in our knowledge on how best to reach the poor in the health sector. In order to fill this gap, more work is needed along the lines of the above studies related to health sector inequalities and public policy. There is necessity to encourage the development of insurance companies, pension funds, and funds for public health care education, which have not yet been properly undertaken.
Keywords: I11; I12; I18; D63; 330; poverty; inequality; health; income distribution; Gesundheit; Armut; Einkommensverteilung; Schätzung; Armenien